The Orientation Mobility Social Communication (OMSC) Learning Based Universal Design for Learning: Optimizing the Potential of Students with Multiple Disabilities and Visual Impairments (MDVI) - Sistriadini Alamsyah Sidik; Dedi Mulia; Yuni Tanjung Utami (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Multiple Disabilities with Visual Impairment (MDVI) refers to individuals with visual impairments—ranging from total blindness to partial vision or residual vision—accompanied by additional limitations. These limitations may include cognitive, developmental, hearing, or mobility impairments. Orientation is utilizing functional senses to position oneself relative to significant objects in the surrounding environment. At the same time, mobility refers to the ability to move from one location to another in a practical, precise, and safe manner. Orientation and mobility are interdependent; orientation is ineffective, and mobility cannot function without orientation. Similarly, social and communication skills are interconnected, as communication skills positively impact the social aspects of multiple disabilities with visual impairment (MDVI) students. This study examines the effectiveness of The Orientation Mobility Social Communication(OMSC) based Universal Design for Learning for students with MDVI. Specifically, it explores the application of OMSC learning in a school with a unique setting that researchers in the Banten area used as research objects. The study employs a mixed-methods research approach, integrating qualitative and quantitative methodologies. The findings demonstrate that media and subject matter experts validated the developed instructional guide, and its trial implementation with students revealed improvements in OMSC skills. These improvements were observed through graphical analyses during baseline 1, intervention, and baseline 2 phases. The study concludes that implementing The Orientation Mobility Social Communication (OMSC) Learning Based Universal Design for Learning is effective for MDVI students, as evidenced by enhancing their OMSC skills during the intervention.